Do ethnic roots shape social fit? Evidence from Chinese-Indonesian and non-Chinese-Indonesian students in China - Abidin, Min Hajul; Gong, Xiuquan (Journal of International Students, 2026)
As the number of Indonesian students in China increases, understanding the determinants of their adaptation and sense of social fit (SSF) becomes essential. SSF is one of the key predictors of psychological well-being and academic success. This study had two aims: (1) to identify factors influencing SSF among Indonesian students, and (2) to examine ethnic roots (Chinese vs. Non-Chinese Indonesians) in shaping SSF in China. Using a quantitative design, survey data were collected from Indonesian students across China. Finding show students of Chinese descent reported higher SSF than Non-Chinese descent, and higher Mandarin Chinese proficiency was modestly but significantly associated with stronger SSF. These findings suggest that process-oriented factors especially communicative competence and cultural-linguistic proximity are more consequential for social fit than static status attributes, underscoring the need for sustained language and cross-cultural engagement programs targeting Indonesian and other international students in China.